RSUME is implicated in HIF-1-induced VEGF-A production in pituitary tumour cells - Shan, B. (2012)
The recently cloned small RWD-domain containing protein RSUME was shown to increase protein levels of hypoxia-inducible factor-1a (HIF-1a). The latter is the oxygen-regulated subunit of HIF-1, the most important transcription factor of the cellular adaptive processes to hypoxic conditions. It is also a major regulator of vascular endothelial growth factor-A (VEGF-A), which is critically involved in the complex process of tumour neovascularisation. In this study, the expression and role of RSUME in pituitary tumours was studied. We found that RSUME mRNA was up-regulated in pituitary adenomas and significantly correlated with HIF-1a mRNA levels. Hypoxia (1% O2) or treatment with hypoxia-mimicking CoCl2 enhanced RSUME and HIF-1a expression, induced translocation of HIF-1a to the nuclei and stimulated VEGF-A production both in pituitary tumour cell lines and primary human pituitary adenoma cell cultures. When RSUME expression was specifically down-regulated by siRNA, the CoCl2-induced increase VEGF-A secretion was strongly reduced which was shown to be a consequence of the RSUME knockdown-associated reduction of HIF-1a synthesis. Thus, RSUME plays an important role in initiating pituitary tumour neovascularisation through regulating HIF-1a levels and subsequent VEGF-A production and may therefore be critically involved in pituitary adenoma progression.